2002
DOI: 10.1212/wnl.58.5.758
|View full text |Cite
|
Sign up to set email alerts
|

Functional deficits in patients with mild cognitive impairment

Abstract: These findings indicate that in patients with MCI, the patient's lack of awareness of functional deficits identified by informants strongly predicts a future diagnosis of AD. If replicated, these findings suggest that clinicians evaluating MCI patients should obtain both self-reports and informant reports of functional deficits to help in prediction of long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
355
4
16

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 452 publications
(415 citation statements)
references
References 32 publications
(31 reference statements)
36
355
4
16
Order By: Relevance
“…Thus, self-report ratings of everyday functioning within the MCI groups do not appear to be more discrepant from their informants' ratings than the degree of discrepancy observed between normal controls and their informants. Other groups have also failed to find a significant discrepancy between self-and informant-reported functional abilities within an MCI group (Tabert et al, 2002). In fact, as noted above, in the current study of community dwelling elders, the MCI groups as well as the normals tended to report slightly more functional change than their informants.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Thus, self-report ratings of everyday functioning within the MCI groups do not appear to be more discrepant from their informants' ratings than the degree of discrepancy observed between normal controls and their informants. Other groups have also failed to find a significant discrepancy between self-and informant-reported functional abilities within an MCI group (Tabert et al, 2002). In fact, as noted above, in the current study of community dwelling elders, the MCI groups as well as the normals tended to report slightly more functional change than their informants.…”
Section: Discussioncontrasting
confidence: 50%
“…Given the trend for an association between verbal memory and the DFQ Difference Score, along with the clear discrepancy between raters in the demented group, results suggest that as people gradually become more cognitively impaired their ability to accurately report their functional status diminishes. Other studies have suggested that when a discrepancy between self and informant reported cognitive or functional status is observed in patients with MCI there is an increased likelihood of eventual conversion to dementia (Tabert et al, 2002;Tierney et al, 1996). The finding that, according to informant report, there may be different levels of everyday functional loss across various subtypes of MCI, with the MCI-memory group showing somewhat more functional change than the MCI-non-memory group, warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since functional status is a basic domain of gerontological assessment 8,9 , several specific questionnaires for the assessment of ADL were developed and are commonly utilized 5,6,9,10,11,12 , specially the Kats Index (BADL) 9,10,13 , the Lawton-Brody Index 9,14 and the Pfeffer Index (IADL) 9,14,15 . However, in Brazil, these questionnaires have not yet been systematically utilized.…”
Section: Introductionmentioning
confidence: 99%